LAG3’s Enigmatic Mechanism of Action - Graydon, Colin G.; Mohideen, Shifa; Fowke, Keith R. (Frontiers in Immunology, 2021)
LAG3 is an important immune checkpoint with relevance in cancer, infectious disease and autoimmunity. However, despite LAG3’s role in immune exhaustion and the great potential of LAG3 inhibition as treatment, much remains unknown about its biology, particularly its mechanism of action. This review describes the knowns, unknowns and controversies surrounding LAG3. This includes examination of how LAG3 is regulated transcriptionally and post-translationally by endocytosis and proteolytic cleavage. We also discuss the interactions of LAG3 with its ligands and the purpose thereof. Finally, we review LAG3’s mechanism of action, including the roles of LAG3 intracellular motifs and the lack of a role for CD4 competition. Overall, understanding the biology of LAG3 can provide greater insight on LAG3 function, which may broaden the appreciation for LAG3’s role in disease and potentially aid in the development of targeted therapies.